FRASE PREPOSISI DALAM ARTIKEL JURNAL AKADEMIK PADA ENGLISH TEACHING FORUM VOLUME 41, NO.4, TAHUN 2003 - REHATTA, BETHLINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT Â The research entitled â€œPrepositional Phrases in Academic Journal Article of the English Teaching Forum, Volume 41, No.4, 2003â€ is an attempt to identify, classify, and analyze the types of prepositional phrases in terms of forms and meanings in academic journal article. The method used in this research is descriptive qualitative method. The theories of Aarts and Aarts (1982), Frank (1972), and Foley and Hall (2003) were used in this research. The data of research were collected from three (3) different articles in journal of English Teaching Forum Volume 41, Number 4, 2003, and were identified, classified, and analyze in terms of forms and meanings. The results of this research show that there are 280 prepositional phrases, which classified in terms of form: the preposition can be followed by noun, noun phrase, pronoun, V+ing, Wh-clause, and prepositional phrase. In terms of meanings, it is divided into three: place, time (position), and place (direction). Â Keywords: Prepositional phrases, meaning and form, academic journal article.